Tuberactinomycin antibiotics: Biosynthesis, anti-mycobacterial action, and mechanisms of resistance - Laughlin, Zane T.; Conn, Graeme L. (Frontiers in Microbiology, 2022)
The tuberactinomycins are a family of cyclic peptide ribosome-targeting antibiotics with a long history of use as essential second-line treatments for drug-resistant tuberculosis. Beginning with the identification of viomycin in the early 1950s, this mini-review briefly describes current knowledge of tuberactinomycin structures and biosynthesis, as well as their past and present application in the treatment of Mycobacterium tuberculosis. More recent studies revealing details of their mechanism of action on the ribosome as well as resistance mechanisms that have emerged since their introduction into the clinic are also discussed. Finally, we describe future potential applications of these drugs given the context of their recent removal from the World Health Organization’s List of Essential Medicines.